Matrizes: uma aplicação no ensino médio a partir de transformações geométricas - Costa Filho, Egidio (2013)
The study of matrices in high school is almost always centered on the teaching of operative techniques, same focus given by textbooks that address this issue at this level of education. This text proposes a different approach, showing in a clear and simple way some applications as translation, rotation and scaling.